2020
DOI: 10.3892/ol.2020.11424
|View full text |Cite
|
Sign up to set email alerts
|

Paeoniflorin inhibits cell viability and invasion of liver cancer cells via inhibition of Skp2

Abstract: Paeoniflorin (PF) has been demonstrated to exert tumor suppressive functions in various types of human cancer. However, the mechanisms of PF-mediated anti-tumor activity have not been fully elucidated. S-phase kinase associated protein 2 (Skp2) has been characterized as an oncoprotein that contributes to carcinogenesis. Therefore, the inhibition of Skp2 may be a useful approach for the treatment of various types of human cancer. The present study explored whether PF inhibited the expression of Skp2 in liver ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…In consistent with the previous report [14,15], CP-25 significantly suppressed cell proliferation, induces cell apoptosis, and enhances the efficacy of 5-Fu in HCC in vivo and in vitro. These results indicated that combination administration of CP-25 and 5-Fu in certain degree may be a potent therapeutic regimen to treat HCC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In consistent with the previous report [14,15], CP-25 significantly suppressed cell proliferation, induces cell apoptosis, and enhances the efficacy of 5-Fu in HCC in vivo and in vitro. These results indicated that combination administration of CP-25 and 5-Fu in certain degree may be a potent therapeutic regimen to treat HCC.…”
Section: Discussionsupporting
confidence: 92%
“…International Publisher used as an herbal medicine to treat arthritis, systemic lupus erythematosus (SLE), fibrosis, hepatic granuloma, diabetic nephropathy (DN) and cancer [10][11][12][13][14][15]. Meanwhile, the anti-inflammatory and immunoregulatory effects of CP-25 have been verified in many studies [16][17][18].…”
Section: Ivyspringmentioning
confidence: 99%
“…Paeoniflorin is a monoterpene glycoside with various anti-cancer activities and is derived from Paeonia lactiflora . Studies have shown that paeoniflorin has broad-spectrum anti-tumor activities against various cancers ( 76 ), including those of liver ( 77 ), lungs ( 78 ), breast ( 79 ), and pancreas ( 80 ). miR-124 levels are significantly increased in paeoniflorin-treated MGC-803 cells, which inhibits PI3K/Akt and p-STAT3 expression.…”
Section: Active Ingredients Of Chinese Medicine Targeting Mirna Inhibmentioning
confidence: 99%
“…or Paeonia veitchii Lynch, which have been used to treat various liver diseases in the traditional medicine of China for many years [ 17 ]. Moreover, it has been verified, in recent research, that PF can protect the liver, prevent non-alcoholic fatty liver disease, relieve liver fibrosis, and inhibit hepatocellular carcinoma through the activities of anti-inflammatory, anti-oxidative stress, and anti-apoptosis [ 18 , 19 ]. Our studies also proved that PF demonstrates the significant effect of cholestasis alleviation via multiple pathways [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%